(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
In this essay I try to show a cultural practice of the Lenca people of Honduras. Focusing exclusively on the Guancasco or Paizanasgo of the municipalities of Ojojona and Lepaterique, in the department of Francisco Morazán. I try to show generalities that are of interest for in-depth research on the subject